Synthesis and properties of some S-derivatives of 4-phenyl-5-((5-phenylamino-1,3,4-thiadiazole-2-ylthio)methyl)-1,2,4-triazole-3-thione - A. S. Hotsulia; S. O. Fedotov (Zaporozhye State Medical University, 2019)
Studies in the field of chemistry and pharmacology of derivatives of thiadiazole and 1,2,4-triazole are promising and relevant, which is associated with significant success in creating new drugs based on them. The combination of these heterocycles in one molecule makes it possible to increase the probability of detecting substances with a certain type of biological activity among the synthesized compounds.The aim of the work was to optimize the synthesis and study of the properties of S-alkyl derivatives of 5-R-4-phenyl-1,2,4-triazole-3-thione, containing a thiadiazole fragment in their structure, as well as the prediction of possible biological activity to rating the prospects of further studies in vivo and in vitro.Materials and methods. As a key starting reagent, 3-amino-1-phenylthiourea was used. Using the reaction between the starting reagent and carbon disulfide in DMF, thion was obtained, which was further alkylated with isopropyl chloroacetate. The resulting reaction product was then used for subsequent transformations using hydrazinolysis reactions, nucleophilic addition of phenylisothiocyanate and intramolecular alkaline heterocyclization. A number of S-derivatives of the obtained 4-phenyl-5-((5-phenylamino-1,3,4-thiadiazole-2-ylthio)methyl)-1,2,4-triazole-3-thione were synthesized by the interaction with haloalkanes in the presence of an equivalent amount of alkali in alcoholic medium. The structure of the obtained compounds was confirmed by elemental analysis, 1H NMR spectroscopy, and IR-spectrophotometry. The individuality of substances was established by high performance liquid chromatography. For the synthesized substances, an individual calculated screening was performed using the PASS Online® software product.Results. The procedure for preparing 4-phenyl-5-((5-phenylamino-1,3,4-thiadiazole-2-ylthio)methyl)-1,2,4-triazole-3-thione was optimized. The optimal synthesis conditions were determined S-alkylderivatives of 4-phenyl-5-((5-phenylamino-1,3,4-thiadiazole-2-ylthio)methyl)-1,2,4-triazole-3-thiol, the structure was established the obtained substances and their physical properties were studied. With the help of computer-assisted prediction Pass Online®, a promising direction for further studies of the biological activity of the target reaction products was determined.Conclusions. A series of S-alkylderivatives of 4-phenyl-5-((5-phenylamino-1,3,4-thiadiazole-2-ylthio)methyl)-1,2,4-triazole-3-thione were obtained, the structure of these compounds was confirmed by physical-chemical methods of analysis. At the next stages of the study, it would be planned to establish indicators of the antimicrobial activity of the synthesized substances.